Contractor's algorithms through CPM networks for optimal financial policies - Yang, Ming-kai; Pichai Nimityongskul; Jearkjirm, Vithool; Ping Kunawatsatit; Chauhan, Gopal; German Academic Exchange Service (DAAD) (Bangkok : Asian Institute of Technology, 1986)
In a CPM network of a construction project, some non critical activities normally exist and they can be shifted in such a way that the project can be more properly and economically executed by the contractor for a specific reason . This technique h as been developed a nd is termed as the well-known resource levelling by shifting the noncritical activities which also gives the contractor a chance to have a minimum financial cost or a minimum amount of fund tied up for a project. With this concept, the contractor may have better financial policies suitable algorithms have been developed in this study. Computer program has also been developed to avoid tedious manual computations and the study has been illustrated through examples.
A thesis study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Critical path analysis; Construction industry -- Planning